Synergistic antioxidant action of vitamin E and rutin SNEDDS in ameliorating oxidative stress in a Parkinson's disease model. (3rd August 2016) - Sharma, Shrestha; Narang, Jasjeet K; Ali, Javed; Baboota, Sanjula
Abstract: Purpose . Oxidative stress is the leading cause in the pathogenesis of Parkinson's disease. Rutin is a naturally occurring strong antioxidant molecule with wide therapeutic applications. It suffers from the problem of low oral bioavailability which is due to its poor aqueous solubility. Methods . In order to increase the solubility self-nanoemulsifying drug delivery systems (SNEDDS) of rutin were prepared. The oil, surfactant and co-surfactant were selected based on solubility/miscibility studies. Optimization was done by a three-factor, four-level (34 ) Box–Behnken design. The independent factors were oil, surfactant and co-surfactant concentration and the dependent variables were globule size, self-emulsification time, % transmittance and cumulative percentage of drug release. The optimized SNEDDS formulation (RSE6) was evaluated for various release studies. Antioxidant activity was assessed by various in vitro tests such as 2, 2-diphenyl-1-picrylhydrazyl and reducing power assay. Oxidative stress models which had Parkinson's-type symptoms were used to determine the antioxidant potential of rutin SNEDDS in vivo . Permeation was assessed through confocal laser scanning microscopy. Results. An optimized SNEDDS formulation consisting of Sefsol + vitamin E–Solutol HS 15–Transcutol P at proportions of 25:35:17.5 (w/w) was prepared and characterized. The globule size and polydispersity index of the optimized formulation was found to be 16.08 ± 0.02 nm and 0.124 ± 0.01, respectively. A significant ( p < 0.05) increase in the percentage of drug release was achieved in the case of the optimized formulation as compared to rutin suspension. Pharmacokinetic study showed a 2.3-fold increase in relative oral bioavailability. The optimized formulation had significant in vitro and in vivo antioxidant activity. Conclusion. Rutin SNEDDS have been successfully prepared and they can serve as an effective tool in enhancing the oral bioavailability and efficacy of rutin, thus helping in ameliorating oxidative stress in neurodegenerative disorders like Parkinson's disease.